1987
DOI: 10.3109/00365528708991918
|View full text |Cite
|
Sign up to set email alerts
|

Gastrin Produces an Immediate and Dose-Dependent Histamine Release Preceding Acid Secretion in the Totally Isolated, Vascularly Perfused Rat Stomach

Abstract: Increasing doses of gastrin 1-17 (G1-17) were administered to totally isolated, vascularly perfused rat stomachs prestimulated with the phosphodiesterase inhibitor isobutyl methylxanthine (IMX). Vascular and luminal histamine outputs and luminal acid output were monitored at short intervals. G1-17 induced an immediate histamine release to the vascular perfusate, preceding the increase in acid secretion by approximately 10 min. Vascular histamine output increased from a base line (IMX only) of 4.0 +/- 0.4 to a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
105
1

Year Published

1991
1991
2016
2016

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 182 publications
(111 citation statements)
references
References 17 publications
5
105
1
Order By: Relevance
“…It should, however, be mentioned that gastrin has a negative tropic effect on the oxyntic D cell (Chen et al 1992) partly explaining the reduction in somatostatin mRNA abundance. The marked increase in HDC mRNA in the oxyntic mucosa simply reflects the well-known stimulatory effect of gastrin on the ECL cell (Sandvik et al 1987) and an increase in HDC mRNA abundance (Sandvik et al 1994).…”
Section: Discussionmentioning
confidence: 99%
“…It should, however, be mentioned that gastrin has a negative tropic effect on the oxyntic D cell (Chen et al 1992) partly explaining the reduction in somatostatin mRNA abundance. The marked increase in HDC mRNA in the oxyntic mucosa simply reflects the well-known stimulatory effect of gastrin on the ECL cell (Sandvik et al 1987) and an increase in HDC mRNA abundance (Sandvik et al 1994).…”
Section: Discussionmentioning
confidence: 99%
“…While a few older studies 8,9 suggested that histamine release could be part of the acid stimulatory process, unequivocal evidence for the immediate and potent effect of gastrin on histamine release was not obtained until 1987. 10 Today, it is clear that the enterochromaf®ne-like (ECL) cell synthesizes histamine in a wide range of species, 11 and that this cell is the only histamine-synthesizing cell with gastrin receptors. 12±14 Moreover, in all species where it has been possible to carry out satisfactory studies, it has been shown that gastrin stimulates the release of gastric mucosal histamine.…”
Section: The Regulation Of Gastric Acid Secretionmentioning
confidence: 99%
“…An alternative theory, the 'transmission' hypothesis (Code, 1977;Black & Shankley, 1987), is that acetylcholine and gastrin act by releasing histamine, which then serves as the final common stimulant of the parietal cell. Support for this idea comes from pharmacological analyses of H-2 receptor antagonist actions in vivo (Black & Shankley, 1987) and from the finding that gastrin and muscarinic agonists release histamine from the totally isolated, vascularly perfused rat stomach, and increase activity of histidine decarboxylase (EC 4.1.1.22; HDC), the enzyme that converts histidine to histamine in the enterochromaffin-like (ECL) cell of the gastric corpus mucosa (Hakanson et al 1974;Sandvik et al 1987Sandvik et al ,1988. The transmission hypothesis currently enjoys considerable support, but the two mechanisms are not mutually exclusive and the relative dominance of one or other almost certainly differs between species.…”
Section: Control O F Gastric Acid Secretionmentioning
confidence: 99%